Human chorioretinal biopsy under controlled systemic hypotensive anaesthesia. Issue 8 (August 1980) - Constable, L. J.; Chester, G. H.; Horne, R.; Harriott, J. F.
Abstract : This paper describes a simplified technique for biopsy of the retina and choroid which had been used in 5 human volunteers. The biopsy was carried out in 4 immediately before enucleation of an eye for malignant melanoma and in 1 patient who was undergoing trabeculectomy for painful glaucoma associated with retinitis pigmentosa. A combination of intravenous mannitol and transient controlled systemic hypotension, induced under general anaesthesia with intravenous sodium nitroprusside, was used in 3 cases and resulted in no vitreous loss and minimal bleeding. In the 2 cases in which hypotension was not used bleeding was a definite problem, but no vitreous loss was experienced.